EVALUATING INTERACTIVE VIDEO UTILIZATION IN ENGLISH FOR TOURISM BUSINESS CLASS - Darmayanti, Putu Sri; Nova, Muhamad (Premise: Journal of English Education and Applied Linguistics, 2022)
Interactive video as one technology product provides an opportunity to enrich students' learning experience. The current study aimed to identify students' perception of interactive video utilization in English for tourism business classes and students' preference in applying interactive video in learning English for tourism business. The interactive videos were embedded in the learning management system, and the students had to utilize them individually. This study employed mixed-method research with an explanatory design. The data were gained through an administering questionnaire survey to 34 students majoring in the Hospitality program and analyzed using descriptive statistics by calculating the frequency of the answer to each question. Then, an interview was also conducted with several students to gain a further explanation of their learning media preferences. The results showed that the students perceived the interactive video positively based on its question layout, quality, and user interface. Furthermore, 94.1% of the students prefer to learn with interactive video than video. The students claimed that the interactive video helps them remember the learning material better, guides them to understand the material, encourages them to focus while watching the video, and makes the learning process more exciting. However, one student argued that the questions needed to be fully understood, and another highlighted the rewind button's unavailability. The result of the study indicated that the utilization of interactive video could be a beneficial learning tool in teaching English to the tourism business. In contrast, the English teacher or lecturer should also consider the students' freedom of learning.